Metropolitan Philaret (Drozdov) and Russian Сhurch Policy in the Holy Land in the 1850s–1860s - Smirnova, Irina (Przegląd Wschodnioeuropejski, 2020)
The issues raised in the article refer to the problems of Church diplomacy of Russia and other great powers in the Middle East in the 1850–1860’s when Russian diplomacy, both secular and church, faced the task of developing new approaches, first of all, in shaping the sphere of Russian interests in the Middle and Far East. Church policy of Russia in the Christian East in the 1850s–1860s is observed through the prism of the position of the Metropolitan of Moscow Filaret (Drozdov, 1782–1867), an outstanding church figure whose position determined the development of Russian church presence abroad not only in the Holy Land, but also in China and North America. The role of Metropolitan Filaret is presented in the forefront of such issues as the development of inter-church relations between the Russian Church with the Patriarchates of the East, the formation of the concept of Russian-Greek, Russian-Arab and Russian-Slavic relations, the interaction and contradictions of the Russian Ecclesiastical Mission and the Russian consulate in Jerusalem.